HUMAN CAPITAL EXCELLENCE IN ISLAMIC INSTITUTIONS: INTEGRATION OF MAQASID AL-SHARIAH, DIGITAL COMPETENCE, AND SUSTAINABLE ORGANIZATIONAL PERFORMANCE - Sari Damayanti; Budiman Budiman; Muhammad Zaky; Sri Dewi Anggadini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This investigation seeks to assess the role of Maqasid al-Shariah, digital proficiency, and enduring institutional effectiveness in fostering workforce excellence within Islamic organizations. In the era of digital transformation, Islamic institutions face significant challenges in enhancing organizational competitiveness while maintaining adherence to Islamic values as the foundation of their operations. Therefore, human capital development should not only focus on improving professional competencies and technological capabilities but also emphasize moral, ethical, and spiritual dimensions. The research adopts a descriptive qualitative methodology, drawing entirely on documentary sources from libraries and scholarly repositories. Data were collected from academic books, scholarly journal articles, and other relevant literature concerning human capital, Maqasid al-Shariah, digital competencies, and organizational sustainability. The findings reveal that the concept of human capital in Islam is holistic, integrating intellectual, professional, social, and spiritual dimensions. This synthesis demonstrates that workforce excellence in Islamic institutions is achieved through the strategic integration of ethical values derived from Maqasid al-Shariah, digital competence, and sustainable organizational objectives, rather than through the independent application of these dimensions. The novelty of this study lies in proposing an integrated conceptual model that connects Maqasid al-Shariah, digital competence, and sustainable organizational performance as a comprehensive framework for developing human capital excellence in Islamic institutions. Consequently, the proposed model offers a strategic framework for Islamic institutions to strengthen competitiveness, achieve organizational sustainability, and promote broader societal welfare in the digital age.